The Competitiveness of Stevia rebaudiana as a Sweetener Alternative in Tawangmangu Subdistrict of Karanganyar Regency - Trisna Wahyu Putri; Any Suryantini; Arini Wahyu Utami (Agro Ekonomi, 2019)
The purpose of this research is to analyze the competitiveness of Stevia agriculture in Tawangmangu Subdistrict, Karanganyar Regency based on its competitive and comparative advantage, as well as to know the effect of government policies on this agricultural product. The basic method used is a descriptive analysis with a quantitative approach. The study involved 14 stevia cultivators as respondents. Sampling was carried out by way of census. The data of the study were collected during one stevia planting season in the course of 2015-2018, with an average planting period of 4 years. The data were collected using Policy Analysis Matrix (PAM) method. The results reveal that stevia farming in Tawangmangu Subdistrict is proven to have a competitive advantage as seen from the value of PP and PCR. It also has a comparative advantage as indicated by its SP and DRCR values. The impact of government policy is apparent from (a) the value of EPC and NPCO pinpointing that there is protection from government policy for domestic farmers who cultivate stevia intensively, especially for output (stevia dried leaves) prices. It is also indicated by (b) the value of NPCI highlighting that the tradable input costs paid by farmers are lower than the cost of tradable inputs that should be paid. This is in accordance with the rule of the Minister of Agriculture of the Republic of Indonesia No.47/Permentan/SR.310/11/2018. It is pivotal that the government provide the stevia farmers with stevia superior seeds to boost the production of high-quality stevia product.